PO.8.184 Will there be a pattern of nailfold video-capillaroscopy in patients with systemic lupus erythematosus?. (27th September 2022) - Mazeda, C; Silva, S; Azevedo, S; Barcelos, A
Abstract : Purpose: Systemic Lupus Erythematosus (SLE) is a chronic and multisystem autoimmune disorder characterized by a heterogeneity of clinical presentations. Clinical expression is the consequence the production of autoantibodies and immune complex vasculitis with endothelial cell damage leading to blood vessel destruction and serious internal organ dysfunction. Nailfold video-capillaroscopy (NVC) is a non-invasive and inexpensive tool that allows assess the microvascular involvement. In SLE only normal patterns and a variety of 'non-specific' capillary abnormalities have been observed. The aim of this study was to evaluate the capillaroscopic changes SLE patients and correlation with organ involvement, laboratory findings and disease activity. Methods: A retrospective study was performed including SLE patients followed in outpatient rheumatology clinic; healthy controls with primary Raynaud's phenomenon (RP) were also enrolled in the study. Socio-demographic and clinical data were collected. Descriptive analysis was performed; p-value≤0.05 was statistically significant. Results: 50 SLE patients (47 female; 3 men) and 50 healthy controls (42 female; 8 men) are included, averaging 47.1±13.6 and 50.3±18.8 years old, respectively (p=0.33). Mean disease duration in SLE patients was 10.6±7.7 years and the most frequent involvements were hematological (64%), cutaneous (64%) and musculoskeletal (56%). Only 18% of patients had RP. All patients with SLE had positive ANAs (36% anti-dsDNA, 32% anti-Ro60, 26% anti-Ro52, 10% anti-SSB, 4% anti-RNP and 4% anti-Smith) and 20% had positive antiphospholipid antibodies. 76% of patients were in remission and the rest had minimal activity according to SLEDAI-2K. In the capillaroscopy findings, SLE patients showed a normal pattern and morphological alterations including tortuous capillaries (30%) and presence of hemorrhages (10%). All controls had normal pattern with tortuous capillaries (5%) and with hemorrhages (2%). In SLE patients, we found statistically significant differences regarding morphology changes in NVC and hematological and nervous system involvement (p=0.04 and p=0.01, respectively) as well as the SLEDAI score (p=0.04). When comparing the SLE patients and healthy controls, significant differences were found in the changes in capillary morphology, Raynaud's phenomenon, and the presence of positive antinuclear antibodies in two groups (p<0.05). Conclusions: As in previous studies, our study showed that nonspecific changes (abnormal morphology, tortuous capillaries and haemorrhages) in NVC are frequent in SLE patients. Some changes seem to be associated with disease activity, but studies with larger sample sizes are warranted and may be beneficial to assess its evolution over time to understand its impact on the clinical outcome.